Methods of Child-Rearing in the Digital Age: A Comparative Study of the Thoughts of Yee Jin Shin and Abdullah Nashih Ulwan - Tantriadi Tantriadi; Muhammad Yunan Harahap; Charles Rangkuti (Jurnal Pendidikan Rafflesia, 2026)
Early exposure to digital devices can interfere with children's brain and emotional development, such as poor long-term memory, weakened concentration, and unstable emotions, while the Book of Tarbiyatul Aulad fil Islam by Abdullah Nashih Ulwan is an Islamic children's education guide that emphasizes seven main aspects: faith, moral, physical, intellect, psychological, social, and sexual. Although written before the advent of digital technology, the principles outlined remain relevant in the face of the challenges of the modern era. The phenomenon of gadgets, social media, and the unlimited flow of information can be a threat to children's moral development, concentration, and moral resilience. Therefore, the values offered by Ulwan—such as the habit of worship, the cultivation of honesty, parental example, environmental control, and full supervision of the development of children's intellect and soul—can be used as a digital framework for Islamic parenting. Through an exemplary approach, habituation, advice, supervision, and discipline, parents are expected to be able to guide children to remain strong in faith and morals even though they live in the midst of the onslaught of digital culture.